‘What Now?’: Genre of the Deuteronomic Code as a Model for Contemporary Theological Ethics - Cash, Emily M. H. (Studies in Christian ethics, 2023)
Typical hermeneutical approaches to the Deuteronomic Code, and to scriptural legal codes more generally, attend to genre either for the sake of historical-critical concerns as an end in themselves, or as a gateway to abstracted content. This article argues, conversely, that the genre of the code is not disconnected from its content, and that its form—imaginative, pragmatic propositions based on communal hope—can and should be imitated in the practice of theological ethics. As best seen in Deuteronomy 15, the communicative genius of the code is that it (1) imagines a specific, viable future, (2) empowers moral agency, (3) forges communal identity, and (4) addresses unique historical situations. Appropriating the genre, rather than the content, thus has unique potential to give traction to modern ethical scholarship through conscious, kerygmatic contingency.